Trends in atherosclerotic cardiovascular disease and lipid management: a population-level observational cohort study in Wales - Daniel Harris (European Journal of Preventive Cardiology, 2024)
Aims: European clinical guidelines recommend that patients with atherosclerotic cardiovascular disease (ASCVD), including ischaemic heart disease (IHD), stroke, and peripheral arterial disease (PAD), are prescribed lipid lowering treatment (LLT) and treated to target low-density lipoprotein cholesterol (LDL-C) levels. This study aimed to document trends in ASCVD, including treatment, monitoring, and achievement of target LDL-C. Methods and results: A retrospective observational population study was performed using linked healthcare data (2010–22). Over the study period, the number of patients with ASCVD increased from 181 153 to 207 747 (8882 to 9398 per 100 000). The proportion of patients prescribed LLT decreased from 75.3% in 2010 to 67.1% in 2022; high-intensity statin therapy increased from 9.4 to 25.2%, while non-high-intensity statin therapy decreased from 59.6 to 38.2%. The prescription of high-intensity statin therapy was consistently higher amongst patients with IHD (10.9% in 2010 increasing to 28.0% in 2022) than in patients with stroke (4.7–21.6%) or PAD (3.9–10.6%). The proportion of cases with documented LDL-C decreased from 58.0% in 2010 to 49.3% in 2022. Of those with documented LDL-C in 2022, 44.0% achieved LDL-C < 1.8 mmol/L, including 45.2% of those with IHD, 42.0% of those with stroke, and only 32.8% of those with PAD. Conclusion: Prescription of LLT, including high-intensity statin therapy, documentation of LDL-C, and achievement of target LDL-C levels was relatively low, especially in PAD patients. Although target achievement in ‘tested patients’ increased over time, the proportion of patients undergoing lipid testing declined. More rigorous lipid management requires prioritisation, especially for PAD and stroke patients.